Socialization of the Benefits of Continuing Higher Education at the Jayapura Regional Development Agricultural Vocational School - Jelatu, Herman; Septikasari, Dian; Witriah, Witriah (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The demand for development and progress in science and technology, without a doubt, is due to the success of the education system from time to time. Education is the main asset that must be owned by everyone. The level of education of a person will have an impact on his life. Interest in continuing education to a higher level is now getting lower. This phenomenon is often found in the Papua region, especially in the city of Sentani. The role of the community, especially teachers, in educating the importance of higher education in the world of education is very necessary. By educating through teachers, of course, it provides stimulus for students, so that they are able to make decisions about their education. Through socialization activities, community service activities produce: 1) the importance of pursuing higher education has been understood; 2) the benefits of continuing education to a higher level have been understood. In general, the interest of students at the Jayapura Regional Development Agricultural Vocational School increased after receiving an explanation of the benefits of continuing education to a higher level.